The chicken or the egg: Technology adoption and network infrastructure in the market for electric vehicles - Nathan Delacrétaz; Bruno Lanz; Jeremy van Dijk (University of Neuchâtel, Institute of Economic Research (IRENE), 2020)
We document non-linear stock effects in the relationship linking emerging technology adoption and network infrastructure increments. We exploit 2010-2017 data covering nascent to mature electric vehicle (EV) markets across 422 Norwegian municipalities together with two complementary identification strategies: control function regressions of EV sales on flexible polynomials in the stock of charging stations and charging points, and synthetic control methods to quantify the impact of initial infrastructure provision in municipalities that previously had none. Our results are consistent with indirect network effects and the behavioral bias called "range anxiety", and support policies targeting early infrastructure provision to incentivize EV adoption.
Keywords: L14; D62; L91; O33; Q48; Q55; Q58; 330; Technology adoption; network externality; electric vehicles; charging infrastructure; two-sided markets; behavioral bias; range anxiety; environmental policy